Dampak Positif dan Negatif Etika Informasi dalam Media Sosial: Sebuah Penelitian Kualitatif dengan Metode Studi Literatur - Hendi Sama; Angeline Angeline; Gary Phua; Rahel Rahel; Stephanie Stephanie (Universitas Bandar Lampung (UBL), 2023)
Positive and Negative Impacts of Information Ethics in Social Media: A Qualitative Study with Literature Study Method - Social media is a platform that facilitates online interaction between one person and another person or group. In our digital age, where individuals have made this platform a daily necessity that aids them in carrying out, learning new things, and strengthening interpersonal ties, this media is crucial. This research demonstrates how information ethics in social media can increase people's sense of responsibility and knowledge. Everyone must use social media responsibly, and any information that has been disseminated carries risks. Information ethics regulations already have certain rules to address related issues.